How ESG activities foster green innovation and sustainable competitive advantage: insights from public and private companies using multi-group PLS-SEM - Widyantoro, Tjatur; Rusmanto, Toto; Warganegara, Dezie Leonarda; Furinto, Asnan (Frontiers in Sustainability, 2025)
This study investigates the role of environmental, social, and governance (ESG) activities in driving green innovation and achieving sustainable competitive advantage, with a comparative analysis of private and public companies. Data were collected from 114 companies (79 private and 35 public) in Indonesia between August and September 2024. Data were collected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Multi-Group Analysis (MGA) conducted via the Smart PLS 4.0 software. The findings reveal that ESG activities are positively directly associated with sustainable competitive advantage, and this connection is only significant for private companies. ESG activities are also directly related to green innovation, and this relationship is more pronounced in public companies. Green innovation is positively associated with sustainable competitive advantage, and this relationship is notably stronger in public company groups. Additionally, green innovation plays a mediating role in the relationship between ESG activities and sustainable competitive advantage, and this model is more dominant in the sample group of public companies. This study provides valuable insights for managers and policymakers in developing countries on leveraging ESG activities as a strategic tool to enhance green innovation and competitive advantage. Furthermore, it offers a refined understanding of how organizational types (public versus private) shape these outcomes.